Model Integrasi Pembelajaran Orang Dewasa dalam Pendidikan Kesetaraan: Studi pada PKBM Kedondong - Muhammad Rizki; Norhidayat Norhidayat; Mustangin Mustangin; Ridwan Ridwan (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to analyze the implementation of andragogy principles in the Learning of the Package C Equality Program at Community Learning Centers (Pusat Kegiatan Belajar Masyarakat Kedondong/PKBM Kedondong). The method used in this study is a qualitative method in order to adjust to the purpose of this research, which is to examine more deeply how to apply the principle of andragogy in the Package C Equality Program at PKBM Kedondong. The techniques used in collecting data were interviews with informants of Package C Equality Education Tutors, residents studying Package C Equality Education, and PKBM Kedondong managers. Data analysis techniques use Data Reduction, Data Presentation, and Conclusion Drawn. Data validity checks are carried out using triangulation techniques and sources. The results of the study show that the implementation of the principle of andragogy in the Package C Equality Education Program at PKBM Kedondong has gone well and is in accordance with the characteristics of adult students. The principle of need-to-know is applied to know what adult learners need. Self-Concept is the active involvement of adult learners in the learning process. Experience as a Learning Resource is used as a discussion material during the learning process. Learning Readiness is applied to conduct mapping in order to find out the ability and how ready adult students are to learn. A Learning Orientation Centered on Real problems that adult learners are facing. And Internal Motivation is applied as a reference for educators to maintain the motivation and enthusiasm for learning of adult students.